2021
DOI: 10.25273/pe.v11i2.10575
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between mathematical disposition and independent learning in distance learning success: An ex post facto study

Abstract: This study uses an ex post facto design with the aim of knowing the interaction between the independent variables (mathematical disposition and learning independence) as a determinant of the dependent variable (learning outcomes). The sample of this study was 32 elementary school students. The data was taken through a questionnaire method and a written test. Data analysis through two-way ANOVA test with interaction factors. The results showed that was an interaction between the independent variables (mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Descriptive analysis was performed on the dataset, the essence was to extract meaningful conclusions. This numerical approach described the information on central tendency, distribution's shape and width of the distribution of data Kusmaryono et al 18 The measure of variation is an indication of the degree to which the scores are either clustered or spread out in the distribution. Standard Deviation shoed the measure of variation from the mean or central points of the distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive analysis was performed on the dataset, the essence was to extract meaningful conclusions. This numerical approach described the information on central tendency, distribution's shape and width of the distribution of data Kusmaryono et al 18 The measure of variation is an indication of the degree to which the scores are either clustered or spread out in the distribution. Standard Deviation shoed the measure of variation from the mean or central points of the distribution.…”
Section: Methodsmentioning
confidence: 99%
“…An interaction between mathematical disposition and independent learning in distance learning success using an ex-post factor study was conducted by Kusmaryono et al, 18 the study showcased the interaction between mathematical disposition and learning independence on learning outcomes of elementary school students in distance learning, the study concluded that the level of mathematical disposition was high and independent learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Independent Learning is a situation where students have the desire to compete, are able to make decisions, and take initiative in overcoming the problems they face. The attitude of independence is not possessed by students quickly but requires self-awareness, habits, and gradual discipline exercises (Broad, 2006;Kusmaryono et al, 2021). So educators must focus on strategic efforts to train students to have independent learning.…”
mentioning
confidence: 99%
“…They will dare to express their opinion, be critical, and be able to solve their own problems (Facione, 2000). The attitude of independent learning makes students trained and has the (Knowles, et al, 2005in Kusmaryono et al, 2021, and has met the criteria of validity test (person's product-moment) and reliability test (Cronbach's alpha) (Isaac & Chikweru, 2018).…”
mentioning
confidence: 99%